Tinjauan Pustaka Sistematis Employee Stock Option - Hidayat, Yusuf Murtadlo; Solikin, Ikin; Purnomo, Budi Supriatono; Alamanda, Dini Turipanam (Business Education Program of Universitas Pendidikan Indonesia, 2022)
Employee stock options are discussed not only by researchers in the field of finance, but also from human resources, to psychology. This study aims to fill the research gap related to ESO by conducting bibliometric analysis on articles from the Google Scholar database. A total of 151 articles were selected from the 175 articles found with a range of publication years 2002-2021. The selected articles are classified based on the relevance of the title and abstract. In addition, it is also classified by publisher. Keywords found and related to ESO are grouped based on relevance and frequency of occurrence in order to obtain three groups of keyword elements.